2013
DOI: 10.1002/bdm.1807
|View full text |Cite
|
Sign up to set email alerts
|

Choice Blindness and Preference Change: You Will Like This Paper Better If You (Believe You) Chose to Read It!

Abstract: Choice blindness is the finding that participants both often fail to notice mismatches between their decisions and the outcome of their choice and, in addition, endorse the opposite of their chosen alternative. But do these preference reversals also carry over to future choices and ratings? To investigate this question, we gave participants the task of choosing which of a pair of faces they found most attractive. Unknown to them, we sometimes used a card trick to exchange one face for the other. Both decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 43 publications
11
64
2
Order By: Relevance
“…Experiment 1 demonstrated that the misinformation effect could be elicited from participants by telling them they had reported remembering episodic details in a different way from how they had earlier reported remembering those details. Experiment 2 generalized these findings to another memory task, eyewitness identification, and demonstrated that blindness to the manipulation, rather than mere exposure to the manipulation, drives subsequent memory change, consistent with previous theoretical and experimental work (Johansson et al, 2014;Sagana et al, 2014;Tousignant et al, 1986). We call this novel consequence of choice blindness on eyewitness memory memory blindness: When witnesses are exposed to manipulated versions of their own memory reports, they often fail to notice the manipulation, and their memories often change to be consistent with those altered reports.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Experiment 1 demonstrated that the misinformation effect could be elicited from participants by telling them they had reported remembering episodic details in a different way from how they had earlier reported remembering those details. Experiment 2 generalized these findings to another memory task, eyewitness identification, and demonstrated that blindness to the manipulation, rather than mere exposure to the manipulation, drives subsequent memory change, consistent with previous theoretical and experimental work (Johansson et al, 2014;Sagana et al, 2014;Tousignant et al, 1986). We call this novel consequence of choice blindness on eyewitness memory memory blindness: When witnesses are exposed to manipulated versions of their own memory reports, they often fail to notice the manipulation, and their memories often change to be consistent with those altered reports.…”
Section: Discussionsupporting
confidence: 78%
“…Johansson et al (2014) found that when participants selected which of two faces they found more attractive, if they were then exposed to the choice blindness manipulation, many would later find the initially unselected face to be more attractive. In other words, the manipulation caused a change in preference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These conditions allow us to conclude that the feedback is the cause of the directional emotional change observed in our study. As such, our result reinforces the wider framework of self-perception theory: that we use our own actions to help infer our beliefs, preferences, and emotions (34,35). Although we do not necessarily react the same way to emotion observed in ourselves and that observed in others, in both cases, we often use the same inferential strategies to arrive at our attributions (12, 36, 37).…”
Section: Discussionsupporting
confidence: 78%